Biomechanical State of the Operated Thoracolumbar Junction in Lateroflexion - Nekhlopochyn, O.S.; Cheshuk, Ye.V.; Vorodi, M.V.; Tsymbaliuk, Ya.V.; Karpinskyi, M.Yu.; Yaresko, O.V. (TERRA ORTHOPAEDICA, 2022)
Summary. The zone of the thoracolumbar junction is the most susceptible to traumatic injuries due to anatomical and physiological features. Accordingly, the stabilization of this section of the spine requires high reliability. Objective: to study the stress-strain state of the model of the thoracolumbar spine after resection of Th12-L1 vertebrae with different types of transpedicular fixation under lateroflexion. Materials and Methods. Mathematical finite element model of a fragment of the human thoracolumbar spine (Тh9-L5) was developed. We modeled the result of decompressive-stabilizing surgery with total removal of Th12-L1 vertebrae including installation of vertebral body replacing implant and fixation with a transpedicular system using 4 pairs of screws. Lateroflexion was modeled by applying a load of 350 N. Results. When evaluating the model without crosslinks and using monocortical pedicle screws, it was found that the maximum loading values in Th10, Th11, L2, and L3 vertebral bodies were 3.4, 2.0, 3.5, and 8.6 MPa, respectively; loading on pedicle screws installed in the indicated vertebrae was 48.4, 48.3, 23.3 and 43.5 MPa. When using bicortical screws without crosslinks in the vertebral bodies, the values were 3.1, 2.5, 3.8, 9.6 MPa and 49.9, 51.9, 25.8, 44.8 MPa, respectively; when using a combination of short screws and crosslinks in the vertebral bodies, the values were 3.2, 2.0, 2.6, 7.5 MPa and 47.6, 47.5, 22.6, 41.2 MPa, respectively; when using crosslinks and bicortical screws, the values were 3.0, 2.2, 2.7, 8.8 MPa and 48.3, 49.6, 24.3, 42.5 MPa, respectively. Conclusions. In lateroflexion, monocortical pedicle screws cause lower critical loading rates compared to long screws at all control points of the model. Crosslinks help to reduce stress levels. The use of monocortical pedicle screws in combination with transverse ties seems to be the most biomechanically effective in lateroflexion.